GAMBARAN KEWARGAAN DIGITAL PADA SISWA MADRASAH ALIYAH NEGERI BERDASARKAN PERSPEKTIF GENDER - Ricca Angreini Munthe; Raihani Raihani; Harris Simaremare (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
ABSTRACTThe rapidly developing digital media has currently been forcing every individual to become a digital citizen. Not exceptionally, students who are at the stage of adolescent development are considered active digital citizens. Research has shown that male students access social media more often than female students. However, it remained unknown how both male and female students in Indonesia develop digital citizenship. This study aims to explore differences in the ability of digital citizenship in two State Islamic High School’s (MAN) students in terms of gender. The study used a mixed method approach sampling 394 students from two madrasah in Bandung. In the quantitative phase, a survey questionnaire was distributed to the sampled students from which six groups of students were selected to participate in the qualitative phase. An FGD was conducted with each of the six groups to understand further their ability in digital citizenship. The results showed female students’ ability in digital citizenship is higher than male. Both male and female students are strong in the aspect of digital security; but they are weak in digital wellbeing and digital civic engagement respectively. This study hopefully contributes to the curriculum development in MAN by taking into account the differences in order to create more effective digital citizens. Keyword: digital citizenship, male, female